Imperialism of the Mind: Decolonial Theological Approaches to Traumatic Memory - Edwards, Stephanie C. (Political theology, 2023)
Frantz Fanon’s call to clear the “rot” of mental imperialism takes on even greater importance in light of emerging neuroscientific research regarding intergenerational trauma. Read through a decolonial theological lens, epigenetic trauma reveals that basic assumptions regarding the independent human person occlude foundational truths. Individuals are fundamentally connected to others in a way that can create ground for a thicker description of “shared humanity” and for liberatory practices of memory. Political theology provides a necessary space to forge theoretical and practical connections between the personal and political natures of race, trauma, and god-talk that are essential to move toward justice. Exploring multiple aspects of being – biological, decolonial, theological, future – I suggest that building communities of Christian enfleshed counter-memory is one potential path toward decolonizing theology and addressing the wounds of colonization through social transformation.